Hydroelectric Power and Anishinaabe Diets: What Oral Testimony Suggests About Managing Food (In)Security on Reserve : Arcadia: Explorations in Environmental History, Summer 2020, no. 33: Hydroelectric Power and Anishinaabe Diets: What Oral Testimony Suggests About Managing Food (In)Security on Reserve - Mehltretter, Samantha; Luby, Brittany; Bradford, Andrea (Rachel Carson Center for Environment and Society, Munich, Germany, 2020)
The arrival of settlers on the Winnipeg River in Northwestern Ontario resulted in drastic changes to the natural system’s ecology and the livelihood of First Nations like Niisaachewan Anishinaabe Nation (NAN). Community members emphasize the loss of manomin (“wild rice” in English), a complex carbohydrate, in histories of colonial contact, and bodily and economic decline. Elders at NAN attribute manomin decline specifically to changes to water level patterns in the twentieth century. Listening to Anishinaabe histories inspires new approaches to addressing food (in)security on reserve, encouraging researchers to address declining yields from the water—not just the land.